Value Relevance of Asset Revaluation Disclosure - Yossi Diantimala; Hafiez Sofyani (Journal of Accounting and Investment, 2020)
Abstract:Research aims: The paper aims to examine the value relevance of asset revaluation disclosure after seven years of implementation of international accounting standards (IAS). This paper highlights the implementation of SFAS 16 which is converged to IAS 16 regarding fixed assets. The SFAS 16 requires companies to disclose the value of fixed assets according to market values if the book value is significantly different from the market value.Design/Methodology/Approach: We analyze 46 non-financial companies that employ the revaluation model during 2012-2018. As benchmarks, we randomly collect 46 non-financial companies that d0 not revaluate their assets during the period. To investigate the value relevance of upward asset revaluation disclosure, we approximate the relationship between and the effect of upward asset revaluation disclosure and stock price by employing Ohlson modified model (1995).Research findings: We suggest that disclosure of upward asset revaluation is value-relevant. The SFAS 16 states that an upward asset revaluation increases the value of equity and assets. Furthermore, we suggest that the information of the book value of equity, net income, and earnings of asset revaluation firms is value-relevant. The results show that the information of the book value of equity and earnings are more value-relevant than upward asset revaluation disclosure and net income.  Theoretical contribution/Originality: Our study contributes to filling the gap of previous results related to the value relevance of fair value disclosure of fixed assets.Practitioner/Policy implication: This research gives an input for financial accounting standards development in Indonesia, particularly regarding the issue of asset revaluation.Research limitation/Implication: Only 46 non-financial companies that employ the revaluation model during 2012-2018. Thus, our study has a small sample size